2014
DOI: 10.3109/14767058.2014.905909
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intravaginal misoprostol and intracervical Foley catheter alone or in combination for termination of second trimester pregnancy

Abstract: The present results confirmed the high success rate with the shortest induction to abortion interval with a combined use of intracervical Foley catheter and misoprostol for termination of second trimester pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…Enrolled women were equally allocated into three groups the first received vaginal misoprostol (n=30), the second received intracervical Foley catheter alone (n=30) and the third received both (n=30). The induction to abortion interval was 7.5 ± 1.25 h in the combined group, compared to 11.76 ± 1.63 h in the misoprostol group and 19.76 ± 1.52 h in the catheter group (p value<0.001) with a success rate of 100% and no major complications reported [9].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Enrolled women were equally allocated into three groups the first received vaginal misoprostol (n=30), the second received intracervical Foley catheter alone (n=30) and the third received both (n=30). The induction to abortion interval was 7.5 ± 1.25 h in the combined group, compared to 11.76 ± 1.63 h in the misoprostol group and 19.76 ± 1.52 h in the catheter group (p value<0.001) with a success rate of 100% and no major complications reported [9].…”
Section: Discussionmentioning
confidence: 82%
“…In countries where mifepristone is not available or affordable, gemeprost or misoprostol alone have been shown to be effective, although a higher total dose is needed and is less effective than the combined regimens [7]. The combination of intravaginal misoprostol and intracervical Foley catheter for second trimester pregnancy termination has been described in two previous studies with conflicting results [8,9]. The aim of this study was to assess the effectiveness, safety and acceptability of intracervical Foley catheter and vaginal misoprostol versus vaginal misoprostol for termination of second trimester pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by (Rezk et al), among 100 patients, 4% had retained placenta, 13% had fever, 8 % had nausea and vomiting, and 8% developed haemorrhage. 18 Other study on 50 patients (Ranjan et al), retained placenta in 10% occurred, fever in 8%, nausea and vomiting in 18%, and 8% had haemorrhage. 9 These results indicate that The patients should start fasting after the start of uterine contractions as they may need general anaethesia for retained placenta, also the process of surgical evacuation should be done with care and under ultrasonographic guidance to avoid uterine perforation and strict aseptic conditions should be emphasized when insertion of Foley's catheter done.…”
Section: Discussionmentioning
confidence: 89%
“…This is in contrast to studies using similar combination (Ranjan et al, Shabana et al and Rezk et al where the induction to abortion interval ranges between 7.5-18 hours in these studies. 9,17,18 This may be because these studies used the same dose of misoprostol that was used in misoprostol termination alone and supplemented this with Foley's catheter insertion. In our study, it was found that a lower dose of misoprostol and a lower frequency of misoprostol were used.…”
Section: Discussionmentioning
confidence: 99%
“…1). Four [15–18] were excluded because the treatment allocation was not randomized, one [19] was excluded because the full text could not be obtained, two [20,21] were excluded because they involved induction of labor in pregnancies with a nonviable fetus, and one [22] was excluded because misoprostol was not used concurrently with a Foley catheter in the combination treatment group. Therefore, eight eligible studies [9–12,23–26] with a total of 1153 patients were included in the present meta‐analysis (Table 1).…”
Section: Resultsmentioning
confidence: 99%